2019
DOI: 10.1039/c8ta10827g
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature, high-speed reactive deposition of metal oxides for perovskite solar cells

Abstract: Perovskite solar cells utilising NiO and TiO2 charge-extraction layers, deposited via high-speed, low substrate-temperature reactive electron-beam evaporation, achieve 15.8% PCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The possibility of improving the PCE after controlling the doping density projected NiO as one of the forthcoming worthwhile HTL candidates. Therefore, various growth mechanisms and thin-film technologies have been explored for its synthesis or/and coating of NiO films in the ambient atmosphere, such as sputtering, 373 atomic layer deposition (ALD), 374 solvothermal growth, 375 sol–gel, 376 e-beam evaporation, 377 reactive e-beam evaporation, 378 atmospheric pressure spatial atomic layer deposition (AP-SALD), 379 and thermal evaporation followed by oxidation. 380 Among them, repeated spin coating has been observed to be a simple and cost-effective method to gain precise control over the thickness and crystallinity of NiO nanostructures, although the residual ligands reduce the coverage of the perovskite absorber, and hence the performance of PSCs.…”
Section: Hole Transport Layer (Htl)mentioning
confidence: 99%
“…The possibility of improving the PCE after controlling the doping density projected NiO as one of the forthcoming worthwhile HTL candidates. Therefore, various growth mechanisms and thin-film technologies have been explored for its synthesis or/and coating of NiO films in the ambient atmosphere, such as sputtering, 373 atomic layer deposition (ALD), 374 solvothermal growth, 375 sol–gel, 376 e-beam evaporation, 377 reactive e-beam evaporation, 378 atmospheric pressure spatial atomic layer deposition (AP-SALD), 379 and thermal evaporation followed by oxidation. 380 Among them, repeated spin coating has been observed to be a simple and cost-effective method to gain precise control over the thickness and crystallinity of NiO nanostructures, although the residual ligands reduce the coverage of the perovskite absorber, and hence the performance of PSCs.…”
Section: Hole Transport Layer (Htl)mentioning
confidence: 99%
“…29 Indeed, we have previously reported a V OC of 1.06 V using the same reactive electron-beam evaporated NiO in inverted PSCs. 26 The high ideality factor that we determine (due to high series resistance and low shunt-resistance) and voltage loss suggest that there are additional non-radiative mechanisms present in our PSC grooves. This could be due to reduced quasi-Fermi level splitting in the perovskite, increased surface recombination at the contact material interfaces, or incomplete coverage of charge-transport materials, all of which can be improved with further optimisation of device fabrication processes.…”
Section: Resultsmentioning
confidence: 70%
“…We have previously demonstrated the effectiveness of reactive e-beam to deposit NiO as a p-type material in conventional planar perovskite solar cells -even without the necessity for thermal annealing. 26 Notably, we have previously found that NiO films fabricated using reactive electron-beam deposition are oxygen-rich; a property previously shown to be promote efficient hole extraction in PSC devices. 21 As an n-type material, we have used C 60 .…”
Section: Papermentioning
confidence: 95%
“…However, there are obvious characteristic peaks of O 1s and Ni 2p in the XPS spectrum, and the intensity of the diffraction peaks regularly decreases as the thickness of the gold electrode increases. [ 31,32 ] We also found that the binding energy of the diffraction peaks of O 1s and Ni 2p shifted toward the lower binding energy with the increased thickness of the gold electrode, which indicated that the electron clouds around the oxygen and nickel atoms become denser. Therefore, we think that NiO x will diffuse into the gold electrode after annealing.…”
Section: Resultsmentioning
confidence: 81%